Implementation of Double Folding Production (PROLIGA) Technology for Improving Shallot Production Using True Shallot Seed (TSS) - Tri Sudaryono; P.E.R. Prahardini (Indonesian Journal of Environment and Sustainable Development, 2020)
Shallot is one of the strategic horticultural commodities that has a very strategic position, considering that this commodity is widely consumed as a daily cooking spice with fluctuating prices. Therefore, it is not surprising if this commodity is a contributor to inflation. To meet the increasing consumption needs is necessary to look for the right strategy to increase domestic shallot production. One strategy considered able to increase shallot production is the implementation of the technology of shallot Double Folding Production (Proliga). Shallot Proliga is a technology to multiply production by using the New Superior Variety (VUB) principle, increasing plant population per area unit with a high planting spacing (10 cm x 10 cm), and optimizing fertilizer input and Plant Pest Organism (OPT) control effectiveness. This research was conducted starting from April to November 2018 in Pelem Village, Pare District, Kediri Regency, East Java. This research applied botanical seeds or TSS of Trisula varieties. The results showed that the implementation of Proliga technology was not only able to double shallot production compared to the technology/ methods commonly used by the local farmers, but also able to improve the farmer income with a B/ C ratio of 1.85.